PENGARUH KOMPETENSI DAN SISTEM INFORMASI TERHADAP KINERJA PEGAWAI DIMEDIASI KOMITMEN ORGANISASIONAL - M., Sumarlin; Akob, Muh.; Alam, Syamsul (LP2M Universitas Bina Bangsa, 2025)
The use and utilisation of information systems in developing countries, such as Indonesia, has not been optimally utilised so that it has an impact on employee performance. This study aims to examine the effect of competence and information systems on employee performance mediated by organisational commitment. The originality of the research is indicated by the limited research that analyses organisational commitment and employee performance by including perceptions of employee competence and information systems. The research problem is the effect of competence and information systems on employee performance with organisational commitment as intervening. This research was conducted at KPPBC TMP B Makassar with a sample unit of 55 employees. The research data were obtained by distributing questionnaires which were then analysed using the SEM-PLS method. The results of data analysis provide evidence that employee competence, information systems, and organisational commitment have a meaningful effect on improving employee performance. It was found that employee competence and reliable information systems proved to increase employee organisational commitment. The role of organisational commitment as an intervening variable is proven in explaining the impact of competence on employee performance, but different results were found on the effect of information systems on employee performance